Potential Associations Between Anthropometric Characteristics, Biomarkers, and Sports Performance in Regional Ultra-Marathon Swimmers: A Quasi-Experimental Study - Iasonas Zompanakis; Konstantinos Papadimitriou; Nikolaos Koutlianos (Applied Sciences)
Background/Objectives: This study aimed to investigate the associations of anthropometric characteristics with performance and potential biomarker changes resulting from a continuous 10 h ultra-marathon swimming effort in regional-level swimmers. Methods: Nine adult male swimmers (age: 43 ± 6 years) participated in a 10 h swim in a 50 m outdoor pool, self-managing their nutrition and hydration breaks. Pre- and post-swim measurements included body weight (BW), body fat percentage (BF%), limb lengths (LL), circumferences (C), lean mass (LM), body mass index (BMI), skinfold thicknesses, heart rate (HR) and blood pressure (BP). Results: A significant reduction was observed in bicep skinfold thickness (Fb) (p = 0.022), while both HR and systolic BP increased post-effort (p = 0.030 and p = 0.045, respectively). Also, most anthropometric parameters, such as BMI, LM, and some C, remained unchanged (p ≥ 0.05). A statistically significant negative correlation was found between post-swim hip circumference (Ph) and total swimming distance (r = –0.682, p = 0.043). Conclusions: While most anthropometric traits remained stable and unrelated to performance, isolated changes in specific biomarkers indicate a physiological response to prolonged exertion. Although pacing and nutritional strategies were not directly examined, observational data—such as consistent swimming rhythm, time allocation for active recovery (AR), and structured carbohydrate intake—suggest these factors may have contributed to performance maintenance and probably the lack of body composition differences after the ultra-marathon effort. These insights are interpretive and align with the existing literature, highlighting the need for future studies with targeted experimental designs.